A Highly Stretchable Liquid Metal Polymer as Reversible Transitional Insulator and Conductor. Issue 23 (11th April 2019) - Wang, Hongzhang; Yao, Youyou; He, Zhizhu; Rao, Wei; Hu, Liang; Chen, Sen; Lin, Ju; Gao, Jianye; Zhang, Pengju; Sun, Xuyang; Wang, Xiangjiang; Cui, Yuntao; et al.
Abstract: Materials with a temperature‐controlled reversible electrical transition between insulator and conductor are attracting huge attention due to their promising applications in many fields. However, most of them are intrinsically rigid and require complicated fabrication processes. Here, a highly stretchable (680% strain) liquid metal polymer composite as a reversible transitional insulator and conductor (TIC), which is accompanied with huge resistivity changes (more than 4 × 10 9 times) reversibly through a tuning temperature in a few seconds is introduced. When frozen, the insulated TIC becomes conductive and recovers after warming. Both the phase change of the liquid metal droplets and the rigidity change of the polymer contribute directly to transition between insulator and conductor. A simplified model is established to predict the expansion and connection of liquid metal droplets. Along with high stretchability, straightforward fabrication methods, rapid triggering time, large switching ratio, good repeatability, the TIC offers tremendous possibilities for numerous applications, like stretchable switches, semiconductors, temperature sensors, and resistive random‐access memory. Accordingly, a system that can display numbers and letters via converting alternative TIC temperature to a binary signal on a computer is conceived and demonstrated. The present discovery suggests a general strategy for fabricating and stimulating a stretchable transitional insulator and conductor based on liquid metal and allied polymers. Abstract : A highly stretchable (680% strain) liquid metal polymer, as a temperature‐controlled reversible transitional insulator and conductor, is demonstrated. After freezing, the liquid metal droplets solidify and expand in volume, whereas the insulating polymer shrinks and becomes rigid, leading to the connection of liquid metal (conductive). It would recover to the initial state (insulative) after heating.